Using a temporary indirect tax cut as a fiscal stimulus: Evidence from the UK - Thomas F. Crossley; Hamish W. Low; Cath Sleeman (Institute for Fiscal Studies (IFS), 2014)
This paper evaluates a novel form of fiscal stimulus: a temporary cut in the rate of Value Added Tax (VAT). In December 2008, the UK cut the standard rate of VAT by 2.5 percentage points for 13 months in an effort to stimulate spending. We estimate the effect of the cut on prices and spending using alternative strategies for identifying the counter-factual. Although firms initially passed through the VAT cut by lowering their prices, at least part of the pass through of the VAT cut was reversed after only a few months. Despite this early reversal, the cut raised the volume of retail sales by around 1% which on its own generates a 0.4% increase in total expenditure. The cut raised retail sales by encouraging consumers to bring forward their purchases and we find a significant fall in sales after the VAT cut ended. Thus an indirect tax cut stimulates significant intertermporal substitution in purchases.
Keywords: H24; H31; E21; E62; 330; fiscal stimulus; passthrough; consumption